2020
DOI: 10.1136/bmjdrc-2020-001476
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of blood glucose level predicts worse outcomes in hospitalized patients with COVID-19: a retrospective cohort study

Abstract: IntroductionWith intense deficiency of medical resources during COVID-19 pandemic, risk stratification is of strategic importance. Blood glucose level is an important risk factor for the prognosis of infection and critically ill patients. We aimed to investigate the prognostic value of blood glucose level in patients with COVID-19.Research design and methodsWe collected clinical and survival information of 2041 consecutive hospitalized patients with COVID-19 from two medical centers in Wuhan. Patients without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
129
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 13 publications
8
129
2
3
Order By: Relevance
“…A small number of observational studies have analyzed the relationship betweenglycemic control and clinical outcomes in patients hospitalized due to COVID-19 with and without diabetes. All of them provide clinical evidence of a correlation between uncontrolled hyperglycemia with poor prognosis and a particularly high mortality rate [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small number of observational studies have analyzed the relationship betweenglycemic control and clinical outcomes in patients hospitalized due to COVID-19 with and without diabetes. All of them provide clinical evidence of a correlation between uncontrolled hyperglycemia with poor prognosis and a particularly high mortality rate [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [7]collected data on 2,041 patients admitted to two medical centers. They compared non-critical patients at admission (n=1,690) to critical patients at the time of admission or at the time of transition from the non-critical group (n=697).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies analyzed clinical characteristics of the patients with diabetes which revealed that the poorly controlled FPG levels could worsen the outcome of the new coronavirus disease [13]. In a retrospective study of 2041 patients with COVID-19, the results revealed that elevation of blood glucose level predicted worse outcomes in hospitalized patients with COVID-19 [14]. Another study indicated that tight glycemic control could improve clinical outcomes in patients with diabetes [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth to mention that glucose variability during the hospitalization, in both diabetes and non-diabetes, also emerged as independent risk factor for a worse prognosis in COVID-19 [4,5].…”
mentioning
confidence: 99%